Reduced Artemisinin Susceptibility of Plasmodium falciparum Ring Stages in Western Cambodia - Witkowski, Benoit (American Society for Microbiology, 2013)
The declining efficacy of artemisinin derivatives against Plasmodium falciparum in western Cambodia is a major concern. The knowledge gap in the understanding of the mechanisms involved hampers designing monitoring tools. Here, we culture-adapted 20 isolates from Pailin and Ratanakiri (areas of artemisinin resistance and susceptibility in western and eastern Cambodia, respectively) and studied their in vitro response to dihydroartemisinin. No significant difference between the two sets of isolates was observed in the classical isotopic test. However, a 6-h pulse exposure to 700 nM dihydroartemisinin (ring-stage survival assay -RSA]) revealed a clear-cut geographic dichotomy. The survival rate of exposed ring-stage parasites (ring stages) was 17-fold higher in isolates from Pailin (median, 13.5%) than in those from Ratanakiri (median, 0.8%), while exposed mature stages were equally and highly susceptible (0.6% and 0.7%, respectively). Ring stages survived drug exposure by cell cycle arrest and resumed growth upon drug withdrawal. The reduced susceptibility to artemisinin in Pailin appears to be associated with an altered in vitro phenotype of ring stages from Pailin in the RSA.